Limiting the Unintended Consequences of High-Stakes Testing. - Yeh, Stuart S. (Education Policy Analysis Archives, 2005)
Interviews with 61 teachers and administrators in four Minnesota school districts suggest that, in their judgment, Minnesota's state-mandated tests were well-aligned with curricular priorities and teachers' instructional goals, emphasizing critical thinking as well as competencies needed to pass the Basic Standards exit exam, and avoiding the type of recall item that would require drill and memorization. This result, i n combination with a survey showing that 85 percent of Minnesota teachers support the exit exam, suggests that Minnesota has been unusually successful in designing a high stakes testing system that has garnered teacher support. The success of Minnesota's model suggests that unintended narrowing of the curriculum due to high stakes testing may be avoided if pressure on teachers to narrow the curriculum is reduced through well-designed, well-aligned exams.